KEKERABATAN GENETIK ANAKAN ALAM ULIN (Eusideroxylon zwageri TEIJSM. & BINN.) MENGGUNAKAN PENANDA RANDOM AMPLIFIED POLYMORPHISM DNA - ILG Nurtjahjaningsih; Sukartiningsih Sukartiningsih; Anna Puspa Amarta Saranti; Purnamila Sulistyawati; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2017)
The study aimed to assess genetic diversity and genetic relationship of ulin wildlings randomly collected from a nursery and originated from Bukit Soeharto natural forest, East Kalimantan. DNA templates were extracted from leaf samples of 1.5 years old wildings. Five RAPD primers consisted 55 polymorphic loci were used for genetic studies. Genetic diversity and relationship were analyzed using GenAlex software. The results showed moderate mean value of genetic diversity (HE=0,345, SE 0,015) of the wildings. Forty eight wildings were clustered in only 3 groups; almost all wildings (65%) were clustered in one main cluster. Moreover, 4 wildlings were clones (8%). In conclusion, the 48 wildings of ulin consisted high genetic relationship and individual clones that reflects the low genetic diversity of this species.